UJI EFEKTIVITAS ANTIBAKTERI ESKTRAK ETIL ASETAT BAWANG DAYAK (Eleutherine palmifolia Merr) TERHADAP STAPHYLOCOCCUS AUREUS DENGAN METODE SUMURAN - Fitriyanti Fitriyanti; Abdurrazaq Abdurrazaq; Muhammad Nazarudin (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Dayak onion (Eleutherine palmifolia Merr.) is a multifunctional medicinal plant for various diseases, one of which is an antibacterial. Dayak Onions (E. palmifolia Merr.) contains an alkaloid, flavonoid, triterpenoid, and saponin compound which has antibacterial properties. This study aims to determine the effect of the ethyl acetate extract of Dayak Onion tubers inhibits the growth of Staphylococcus aureus bacteria. Dayak onion tuber was extracted using ethyl acetate solvent by the maceration method until thick extract was obtained. The concentration extract used were 30 mg/ml;15 mg/ml;7,5 mg/ml;3,75 mg/ml; 1,875 mg/ml; and 0,9375 mg/ml tested for antibacterial effectivity against Staphylococcus aureus using Mueller Hinton Agar (MHA) with the wells method. The result showed that the ethyl acetate of Dayak onion with MEC (Minimum effective concentration) 3,75 mg/ml obtained inhibition zone of 10,367 mm while at the highest concentration of 30 mg/ml had the best antibacterial effectiveness. The effective concentration of ethyl acetate onion of Dayak tuber which is 30 mg/ml obtained inhibition zone of 18,404 mm even in the moderate category.